Melampaui Politik Identitas: Kontekstualisasi Islam Nusantara di EraTeknolologi dan Informasi pada Pendidikan SMK di Pesantren Bustanul Falah Genteng Banyuwangi - Imam Wahyono (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2018)
This Research explores the Islam of Archipelago as an idea that isi dedeveloping in the raising of radical Islam Ideology. Islam leaders assume that Islam Archipelago is an ideologi which is appropriate in accomodating the cultura wealth of Indonesia. But, these ideologi becomes controversial in relation with the term “Archipelago” used in the context. Through ethnograpic approach, this research is done to view Islam of archipelago from the practical perspective in education. The result of this research is the practical formula about Islam of archipelago, appropriates with the development of Indonesia in the middle of information and technology which are developing rapidly.